Problems and alarms of the patient’s relatives served in the bulgarian hospices - S. S. Alexandrova; G. G. Grantcharova (Медицинский вестник Юга России, 2010)
Purpose: The analysis of problems and alarms of the patient’s relatives served in hospices and the services rendered to it.Materials and Methods: Questioning of 190 members of the personnel, 216 relatives and the close patients who were in 29 hospices and 5 branches of the palliative help of Bulgaria in 2008.Results: There is no practice of granting conditions for stay of relatives and maintenance of contacts to relatives after death of the patient in the Bulgarian hospices. Relatives underline absence of free from work of a member of a family and impossibility of reception of long holiday for service of the patient as the basic problems. The basic alarms are connected with a condition of the patient and necessary measures for its service.Summary: Wide informing of the population on various forms hospice’s help and a special attention of the medical personnel to problems of health of relatives are necessary.